PENYELENGGARAAN LAYANAN KEDOKTERAN NUKLIR DI RUMAH SAKIT BERDASARKAN PERATURAN PEMERINTAH NOMOR 5 TAHUN 2021 TENTANG PERIZINAN BERUSAHA BERBASIS RISIKO SERTA ASPEK PERTANGGUNGJAWABANNYA - Parwati, Ni Made (Jurnal Yusthima, 2022)
Government Regulation (PP) Number 5 of 2021 of the Republic of Indonesia specifically regulates the implementation of risk-based company licensing. Licensing is regulated for all business sectors, including the health sector. Hospitals with nuclear medicine services (including therapeutic nuclear medicine and in vivo diagnostic nuclear medicine) that require molecular imaging so that a risk-based approach (RBA) is applied are strictly regulated by the Ministry of Health in accordance with Number 14 of 2021 concerning business actor activity standards and health products. Nuclear medicine will have a broad impact on staff and patients as well as the environment, so it is important to study it from the licensing aspect. The purpose of this paper is to discuss the supervision of the implementation of nuclear medicine in hospitals, focusing on the licensing aspect by outlining legal responsibilities and aspects of accountability. The research method used is normative juridical. This type of research uses library research. The research approach uses a normative approach. The data used is secondary, in the form of statutory regulations and legal expert theories. The supervision of the implementation of nuclear medicine is carried out by the Nuclear Energy Supervisory Agency, referring to Government Regulation Number 5 of 2021 concerning risk-based business permits. The type of business license is determined by the level of risk on which the risk-based business license is based. The government has identified the level of risk based on the business sector. As a result, the issuance of permits must be strictly based on the readiness of all aspects of service support for standard compliance. Hospitals have legal obligations that include health workers in them, namely that clinical practice is limited by the law on medical practice and the law on hospitals so as not to deviate from the standard of the medical profession, which could endanger the lives of patients and health workers. Peraturan Pemerintah (PP) Republik Indonesia Nomor 5 Tahun 2021 mengatur secara spesifik tentang Pelaksanaan Perizinan Perusahaan Berbasis Risiko. Perizinan diatur untuk semua sektor usaha, termasuk sektor Kesehatan. Rumah sakit dengan layanan kedokteran nuklir antara lain kedokteran nuklir terapi dan kedokteran nuklir diagnostik in vivo) yang membutuhkan pencitraan molekuler sehingga diterapkan Risk Based Approach (RBA), hal ini diatur secara tegas oleh Kementerian Kesehatan sesuai dengan Nomor 14 Tahun 2021 tentang Standar Kegiatan Pelaku Usaha dan Produk Bidang Kesehatan. Dengan kedokteran nuklir akan menimbulkan dampak luas bagi petugas maupun pasien maupun lingkungan, sehingga penting untuk dikaji dari aspek perijinannya. Tujuan penulisan ini adalah membahas pengawasan penyelenggaraan kedokteran nuklir di rumah sakit focus pada aspek perijinan dengan menguraikan tanggung jawab hukum maupun aspek pertanggungjawabannya. Metode penelitian yang digunakan adalah yuridis normatif. Jenis penelitian menggunakan library research. Pendekatan penelitian menggunakan pendekatan normatif. Data yang digunakan data sekunder berupa peraturan perundang-undangan dan teori-teori ahli hukum. Pengawasan penyelenggaraan kedokteran nuklir dilakukan oleh Badan Pengawas Tenaganuklir mengacu PP Nomor 5 Tahun 2021 tentang Perizinan Berusaha Berbasis Risiko. Jenis izin usaha ditentukan oleh tingkat risiko yang menjadi dasar izin usaha berbasis risiko. Pemerintah telah mengidentifikasi tingkat risiko berdasarkan sektor usaha. Sehingga penerbitan ijin harus dilakukan secara ketat terhadap kesiapan seluruuh aspek pendukung layanan terhadap kepatuhan terhadap standar. RS memiliki kewajiban hukum termasuk petugas Kesehatan didalamnya yaitu dalam praktek klinis dibatasi oleh UU praktek kedokteran maupun UU RS agar tidak menyimpang dari standar profesi medis yang dapat membahayakan kehidupan pasien maupun petugas Kesehatan.